The origins of complex political organisation in ancient inner Asia - Kim, Hyun Jin author.
1 online resource
Keywords: This book explores the origins of complex political organisation in Inner Asia, which enabled mighty empires, proto-state entities and confederacies such as the Cimmerians, Scythians and the Xiongnu Huns to emerge and dominate large swathes of the Eurasian continent during antiquity.The volume provides readers with an in-depth understanding of the origins and development of the quasi-feudal system of political organisation, which prevailed in Inner Asia during antiquity, how this supported the formation of imperial polities in the steppe zone, and the impact the expansion of these polities had on the politics, history and culture of both ancient Inner Asia and also China, the Middle East and Europe. It examines the historical and archaeological evidence for the Cimmerians and Scythians and their geopolitical impact on western Eurasia, exploring whether the complex political organisation in Inner Asia - which we see later among the Xiongnu and the Huns - originated with them or had even earlier antecedents.The Origins of Complex Political Organisation in Ancient Inner Asia is suitable for students and scholars of Near Eastern history and archaeology, the history and archaeology of Central and Inner Asia, and classical antiquity.